High quality mesh generation for volumetric data processing - Han, Shuchu (2010)
High quality tetrahedral/hexahedral mesh generation is important for a wide range of applications in computer graphics, finite element analysis (FEA), physics-based simulation, and solid modeling. In this thesis, the existing unstructured mesh generation methods, the subdivision algorithms and the tetrahedral remeshing techniques are investigated. Moreover, an isotropic tetrahedral mesh generation method is developed and successfully applied to anisotropic solid texture transfer applications. Besides, a hexahedral shell mesh construction method based on volume polycube map is proposed.